Disparity Analysis Of Foreign And Domestic Investment Realization In West Bandung Regency 2024 - Surya, Sarjito; Ramadhan, Muhammad Mulia; Wahyudin, Dikdik; Somantri, Asep; Sukanta, Tuntun Ariadi (Universitas Indonesia Membangun, 2025)
This study aims to analyze the disparity in the realization of Foreign Direct Investment (FDI) and Domestic Direct Investment (DDI) across subdistricts in West Bandung Regency in 2024. Investment plays a vital role in supporting regional economic development; however, its distribution tends to be uneven, potentially widening interregional development gaps. This research uses a quantitative descriptive approach, employing secondary data sourced from regional investment reports. To measure investment disparity, the Lorenz Curve is applied, providing a visual representation of inequality in investment distribution among subdistricts. The analysis reveals a notable disparity in both FDI and DDI realization, with investment concentrated in specific subdistricts that possess better infrastructure, accessibility, and economic facilities. These findings highlight the urgency for more inclusive and regionally balanced investment policies to reduce spatial inequality and promote equitable development in West Bandung Regency.